Implementation of Work Culture in the General Section of the Regional Secretariat of Sumedang Regency - Aulia Priyani, Jihan; Muliawaty, Lia (Jurnal Polisci, 2024)
In general, employees will be influenced by the variety of resources available, which will encourage them to adopt specific behaviors relevant to the organization. Work culture is the main goal in carrying out government operations, namely changing the attitudes and behavior of human resources to improve performance, as well as acting as a strategic effort in facing various challenges of the business world in the future. The attitudes and behaviors of employees in the General Section of the Regional Secretariat of Sumedang Regency influence the importance of work culture in carrying out government organizational activities. The study aims to know the implementation of Work Culture in the General Section of the Regional Secretariat of Sumedang Regency and the Elements Inhibiting the Implementation of Work Culture in the General Section of the Regional Secretariat of Sumedang Regency. The research method used by the author is a qualitative descriptive method. Data and information collection is done through observation, interviews, and documentation. The study results show that the implementation of work culture in the General Section of the Regional Secretariat of Sumedang Regency has not run well. Judging from several elements and sub-elements of Attitude towards work and behavior at work, the problems found are a need for work ethic, responsible employees, and careful employees. This is undoubtedly an obstacle to the proper implementation of work culture